Comparative analysis of apical microleakage for two obturating materials-resilon and gutta-percha with two resin-based sealers - Rakesh Mittal; Meenu G Singla; Ashima Garg; Sumit Gupta; Anika Bansal (Wolters Kluwer Medknow Publications, 2012)
Aim: The purpose of this in vitro study was to assess the apical sealing ability of Epiphany/Resilon, AH Plus/gutta-percha and their cross combinations-AH Plus + Resilon and Epiphany+gutta-percha. Materials and Methods: Fifty eight extracted human single-rooted mandibular premolars were used and obturated with different combinations of core material and sealer using lateral compaction technique. The groups were as follows: Group-1: Epiphany + Resilon; Group-2: AH Plus + Gutta-percha; Group-3: AH Plus + Resilon; Group-4: Epiphany + Gutta-percha; Group-5: Negative control group. Apical microleakage was assessed with dye penetration method using stereomicroscope. Statistical analysis was performed using one-way ANOVA followed by post hoc test (Bonferroni test), with significance level set at P < 0.05. Results: Results indicated that AH Plus + Resilon had the least microleakage than all the other groups, followed by Epiphany + Gutta-percha group while Epiphany + Resilon group demonstrated the greatest amount of microleakage. Statistical analysis showed significant results (P < 0.05) except for comparison between Group 1-2 and Group 3-4 (P > 0.05). Conclusions: Resilon + AH Plus showed significantly least amount of microleakage and better apical sealing ability as compared to other groups.